Desmoplastic small round cell tumor: from genomics to targets, potential paths to future therapeutics - Magrath, Justin W.; Espinosa-Cotton, Madelyn; Flinchum, Dane A.; Sampath, Shruthi Sanjitha; Cheung, Nai Kong; Lee, Sean B. (Frontiers in Cell and Developmental Biology, 2024)
Desmoplastic Small Round Cell Tumor (DSRCT) is a highly aggressive pediatric cancer caused by a reciprocal translocation between chromosomes 11 and 22, leading to the formation of the EWSR1::WT1 oncoprotein. DSRCT presents most commonly in the abdominal and pelvic peritoneum and remains refractory to current treatment regimens which include chemotherapy, radiotherapy, and surgery. As a rare cancer, sample and model availability have been a limiting factor to DSRCT research. However, the establishment of rare tumor banks and novel cell lines have recently propelled critical advances in the understanding of DSRCT biology and the identification of potentially promising targeted therapeutics. Here we review model and dataset availability, current understanding of the EWSR1::WT1 oncogenic mechanism, and promising preclinical therapeutics, some of which are now advancing to clinical trials. We discuss efforts to inhibit critical dependencies including NTRK3, EGFR, and CDK4/6 as well as novel immunotherapy strategies targeting surface markers highly expressed in DSRCT such as B7-H3 or neopeptides either derived from or driven by the fusion oncoprotein. Finally, we discuss the prospect of combination therapies and strategies for prioritizing clinical translation.